An Interactive Qur’anic Values-Based Affective-Learning Approach to Mitigating School Bullying - Utaminingsih, Esty Setyo; Idammatussilmi, I; Intania , Belita Yoan; Kristiyuana , K (Universitas Muhammadiyah Surakarta, 2025)
Persistent peer bullying in Indonesian primary schools warranted culturally attuned solutions; consequently, a systematic review was conducted to evaluate how interactive programmes embedding Qurʾānic values mitigated bullying. Guided by a pre-registered PRISMA-2020 protocol, seven databases (Scopus, Web of Science, Frontiers, Taylor & Francis, MDPI, Springer, and Google Scholar) were searched for studies published between 2019 and 2025, yielding 330 records, of which 11 empirical studies met the eligibility criteria. The evidence converged into three intervention archetypes digital Qurʾānic storytelling, prophetic-narrative role-play/project learning, and Qurʾān-infused school-climate initiatives that collectively reduced bullying incidents by 30–57 % over 4–12 weeks and increased pupil empathy (Cohen’s d = 0.42–0.88). Although methodological heterogeneity prevailed, all studies reported improvements in peer relations and school climate, suggesting that affective learning grounded in the Qurʾān’s principles of raḥmah, ʿadl, and ukhuwwah fostered prosocial behaviour; however, the paucity of cluster-randomised controlled trials and short follow-ups constrained causal inference. The review concluded that a Qurʾānic pedagogical framework constitutes a culturally congruent complement to secular anti-bullying models, provided that future research incorporates rigorous longitudinal designs. National policy-makers and teacher-education programmes are therefore encouraged to integrate Qurʾānic affective-learning components into anti-bullying guidelines to enhance cultural relevance and long-term sustainability.